2009
DOI: 10.5194/angeo-27-3825-2009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distributions of electromagnetic field variations and injection regions during the 20 November 2007 sawtooth event

Abstract: Abstract. We report multi-spacecraft and ground-based observations of a "sawtooth" event on 20 November 2007. For this event, data from three THEMIS, two GOES, and four LANL spacecraft are available as well as those from extensively distributed ground magnetometers and all-sky imagers. In the present paper we focus on the spatial extents of the electromagnetic and particle signatures of the first "tooth". In this event, auroral images and ground magnetic bays showed two activations: a pseudo onset and a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
2
0
0
Order By: Relevance
“…In contrast, the reconnection simulations showed a more nonlinear effect, with the field‐aligned currents rapidly increasing as the flows were stopped in the near tail and diverted. The bubble simulations further demonstrated that the total amount of the field‐aligned current increased with increasing cross‐tail width of the depleted region, even though the flows might break up into multiple channels. This is consistent with larger substorm wedge currents in sawtooth substorms, which extend over much wider local times than individual ones [e.g., Reeves , ; Cai et al , ; Kasahara et al , ]. The flows commonly break into multiple narrow channels, separated in space and time (consistent with conclusions of Sergeev et al []), while the associated increases in B z accumulate over a wider spatial range and spread both azimuthally and radially, analogous to multiple snowplows that collect snow and dump it into one growing and expanding pile. This picture is consistent with observations that earthward flows, associated with, or preceding, a persistent dipolarization are much more localized than the dipolarizing region, even in a statistical picture [ Miyashita et al , ].…”
Section: Summary and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, the reconnection simulations showed a more nonlinear effect, with the field‐aligned currents rapidly increasing as the flows were stopped in the near tail and diverted. The bubble simulations further demonstrated that the total amount of the field‐aligned current increased with increasing cross‐tail width of the depleted region, even though the flows might break up into multiple channels. This is consistent with larger substorm wedge currents in sawtooth substorms, which extend over much wider local times than individual ones [e.g., Reeves , ; Cai et al , ; Kasahara et al , ]. The flows commonly break into multiple narrow channels, separated in space and time (consistent with conclusions of Sergeev et al []), while the associated increases in B z accumulate over a wider spatial range and spread both azimuthally and radially, analogous to multiple snowplows that collect snow and dump it into one growing and expanding pile. This picture is consistent with observations that earthward flows, associated with, or preceding, a persistent dipolarization are much more localized than the dipolarizing region, even in a statistical picture [ Miyashita et al , ].…”
Section: Summary and Discussionsupporting
confidence: 73%
“…The bubble simulations further demonstrated that the total amount of the field-aligned current increased with increasing cross-tail width of the depleted region, even though the flows might break up into multiple channels. This is consistent with larger substorm wedge currents in sawtooth substorms, which extend over much wider local times than individual ones [e.g., Reeves, 1998;Cai et al, 2006;Kasahara et al, 2009].…”
Section: Summary and Discussionsupporting
confidence: 72%